K4Nb6O17 layered hexaniobate: revisiting the proton-exchanged reaction - Figueiredo, Mariana Pires; Constantino, Vera Regina Leopoldo (Eclética Química, 2022)
The layered hexaniobate of K4Nb6O17 composition and its derivatives comprise nanostructured materials that exhibit suitable properties for application in catalysis, electrochemistry, and energy, for instance. The exchange of K+ cations to obtain the acidic or protonic niobate form is the main route to originate appropriate precursors to promote the hexaniobate exfoliation, yielding a dispersion of thin layers (2D particles) that can be scrolled under exclusive conditions. Hexaniobate presents two regions (I and II), being the former considered more accessible than region II. In this work, the proton exchange efficiency of the K4Nb6O17 was investigated by thermogravimetric analysis coupled to mass spectrometry (TGA-MS) and metal analysis by inductively coupled plasma spectroscopy (ICP). The products of thermal decomposition profile of the HxK(4-x)Nb6O17 phase were isolated at defined temperature values and characterized by X-ray diffractometry and Raman spectroscopy. The cation exchange percentages obtained by TGA-MS (68.0%) and by quantification of deintercalated K+ by ICP (64.0%) are similar and endorse that region II can also be modified and, consequently, contribute to the exfoliation process.